Low-dielectric-loss multilayer ceramic substrate and preparation method thereof

By using alumina composites and other additives of different shapes in the multilayer ceramic substrate, a dense microstructure is formed, which solves the problem of high dielectric loss of the multilayer ceramic substrate, and achieves the effect of reducing dielectric loss and improving signal transmission stability.

CN119707465AActive Publication Date: 2025-03-28HEBEI DINGCI ELECTRONIC TECH CO LTD

Patent Information

Application Number
CN202510212856.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-03-28
Estimated Expiration
2045-02-26

AI Technical Summary

Technical Problem

The dielectric loss of existing multi-layer ceramic substrates is high, resulting in increased substrate temperature, signal transmission attenuation and distortion, affecting the normal operation of electronic components and the accuracy of signal transmission.

Method used

By combining the first alumina (spherical) and the second alumina (flake) of different shapes, combining plasticizers, binders, sintering aids and dispersants, a multi-layer ceramic substrate is prepared to form a dense and orderly microstructure to reduce dielectric loss.

Benefits of technology

It effectively reduces the dielectric loss of multi-layer ceramic substrates, reduces the loss of converting electrical energy into thermal energy, reduces the heating of the substrate, and improves the accuracy and stability of signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of ceramic substrates, and provides a low-dielectric-loss multilayer ceramic substrate and a preparation method thereof. The low-dielectric-loss multilayer ceramic substrate is prepared from, by weight, 90-100 parts of aluminum oxide, 1-3 parts of plasticizer, 3-5 parts of sintering aid, 6-10 parts of binder, 1-3 parts of dispersing agent and 50-60 parts of water, the aluminum oxide is composed of first aluminum oxide and second aluminum oxide, and the first aluminum oxide and the second aluminum oxide are different in form. According to the technical scheme, the problem of high dielectric loss of the multilayer ceramic substrate in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic substrates, and in particular to a low dielectric loss multilayer ceramic substrate and a preparation method thereof. Background Art

[0002] Multilayer ceramic substrate is a new type of electronic packaging material made by printing, stacking and sintering multiple ceramic sheets. These ceramic sheets are usually printed with conductive lines, through holes and other structures to achieve electrical connection and signal transmission between electronic components. With its excellent mechanical properties, high insulation and good thermal stability, multilayer ceramic substrates are widely used in the electronics field.

[0003] At present, the research on multilayer ceramic substrates is mainly focused on improving their comprehensive performance. Researchers are constantly exploring new material systems and optimizing preparation processes to achieve higher wiring density, better heat dissipation performance, and stronger mechanical reliability. However, there are still many problems to be solved in the key performance indicator of dielectric loss.

[0004] Dielectric loss refers to the energy lost when a dielectric converts electrical energy into heat energy due to the hysteresis effect of dielectric conductivity and dielectric polarization under the action of an alternating electric field. For multilayer ceramic substrates, high dielectric loss can cause a series of serious hazards. On the one hand, excessive electrical energy is converted into heat energy, causing the substrate temperature to rise, which not only affects the normal working performance of electronic components, but long-term high temperature may also accelerate component aging and shorten the service life of the equipment; on the other hand, high dielectric loss can cause signal attenuation and distortion during transmission, reducing the accuracy and stability of signal transmission. This problem is particularly prominent in high-frequency circuits, which seriously restricts the effective transmission of high-speed, large-capacity data.

[0005] In contrast, multilayer ceramic substrates with low dielectric loss have significant advantages. They can effectively reduce the loss of electrical energy converted into heat energy, reduce the heat generation of the substrate, help maintain the temperature stability of the working environment of electronic components, and improve the reliability and durability of the system; at the same time, low dielectric loss can greatly reduce the attenuation and distortion during signal transmission, ensure high-quality signal transmission, meet the needs of modern electronic equipment for high-speed and high-frequency signal processing, and lay the foundation for the realization of more advanced electronic technology applications. Therefore, it is necessary to develop a multilayer ceramic substrate with low dielectric loss. Summary of the invention

[0006] The present invention provides a low dielectric loss multilayer ceramic substrate and a preparation method thereof, which solves the problem of high dielectric loss of the multilayer ceramic substrate in the related art.

[0007] The technical solution of the present invention is as follows: The present invention proposes a low dielectric loss multilayer ceramic substrate, comprising the following component raw materials in parts by weight: 90 to 100 parts of aluminum oxide, 1 to 3 parts of a plasticizer, 3 to 5 parts of a sintering aid, 6 to 10 parts of a binder, 1 to 3 parts of a dispersant, and 50 to 60 parts of water, wherein the aluminum oxide is composed of a first aluminum oxide and a second aluminum oxide, and the first aluminum oxide and the second aluminum oxide have different forms.

[0008] As a further technical solution, the first alumina is spherical alumina, the second alumina is flaky alumina, and the mass ratio of the first alumina to the second alumina is 2-3:1.

[0009] In the present invention, spherical alumina and flaky alumina are used in combination. The spherical alumina has good fluidity and filling properties. During the preparation process of the multilayer ceramic substrate, it can be tightly stacked in the matrix. The interlayer structure of the flaky alumina can play a barrier-like role to prevent excessive charge migration and the development of polarization. When an electric field is applied, the flaky alumina can limit the movement of charges between layers and reduce the energy loss in the process of charge accumulation and release. By coordinating the mass ratio of the two, the synergistic effect of the two is exerted, and the dielectric loss of the multilayer ceramic substrate is further reduced.

[0010] As a further technical solution, the average particle size of the first aluminum oxide is 3-5 μm, and the average particle size of the second aluminum oxide is 3 nm.

[0011] In the present invention, the spherical alumina particles of 3 to 5 μm are relatively large and can build a basic skeleton structure, while the flaky alumina particles of 3 nm are extremely small and can be filled in the gaps between the spherical alumina particles, forming an extremely compact and ordered microstructure. This structure greatly reduces internal pores and defects, which are key factors in causing electric field distortion and increasing dielectric loss. The compact and ordered structure makes the electric field distribution more uniform, further reducing dielectric loss.

[0012] As a further technical solution, the second alumina is a hydroxymethoxybenzaldehyde compound composite second alumina.

[0013] As a further technical solution, the hydroxymethoxybenzaldehyde compound includes one or more of 4-hydroxy-2-methoxybenzaldehyde, 2-hydroxy-4,5-dimethoxybenzaldehyde, and 4-hydroxy-2,6-dimethoxybenzaldehyde, preferably 2-hydroxy-4,5-dimethoxybenzaldehyde.

[0014] In the present invention, hydroxymethoxybenzaldehyde compounds are used to perform composite treatment on the second alumina. After composite treatment, the surface properties of the second alumina are improved, the surface energy is reduced, and the second alumina particles are more easily and evenly dispersed in the slurry. During the molding process, the evenly dispersed particles can be more densely stacked to form a denser and more ordered microstructure. This dense structure reduces internal pores and defects. When subjected to external force, the stress can be more evenly transmitted throughout the structure, avoiding the generation and expansion of cracks caused by stress concentration, thereby improving the mechanical strength of the ceramic substrate.

[0015] As a further technical solution, the preparation method of the hydroxymethoxybenzaldehyde compound composite second alumina includes the following steps: dispersing the hydroxymethoxybenzaldehyde compound in a solution, adding the second alumina, mixing, filtering and drying to obtain the hydroxymethoxybenzaldehyde compound composite second alumina.

[0016] As a further technical solution, the mass ratio of the hydroxymethoxybenzaldehyde compound to the second alumina is 2~3:20.

[0017] As a further technical solution, the solution is anhydrous ethanol, and the mass ratio of the solution to the second aluminum oxide is 10:1.

[0018] As a further technical solution, the mixing time is 2 hours.

[0019] As a further technical solution, the plasticizer includes one or both of dibutyl phthalate and dioctyl phthalate.

[0020] In the present invention, a plasticizer is added, and the plasticizer gives the green body a certain flexibility, so that it is not easy to be broken by external forces during the molding process. In the preparation of a multi-layer ceramic substrate, the green body may need to undergo lamination, cutting and other process operations. If the green body lacks flexibility, cracks are likely to appear during these operations. The addition of the plasticizer enables it to withstand a certain degree of bending and deformation, ensuring the smooth progress of the molding process.

[0021] As a further technical solution, the sintering aid includes one or more of calcium oxide, yttrium oxide, and cerium oxide.

[0022] In the present invention, sintering aids such as calcium oxide, yttrium oxide, and cerium oxide can reduce the sintering temperature, promote the densification and grain refinement of ceramics, and the dense structure and uniform and fine grains can improve the material's ability to resist external forces and reduce the generation and expansion of cracks. In the preparation of multilayer ceramic substrates, good mechanical properties can ensure that the substrate is not easily damaged during processing and use, thereby improving the reliability of the product.

[0023] As a further technical solution, the binder includes one or more of acrylate, polyvinyl alcohol, and polyvinyl butyral, preferably acrylate.

[0024] In the present invention, a binder is added. The main function of the binder is to form a connecting bridge between ceramic powder particles, enhance the bonding force between them, and firmly bond the dispersed particles together. In the preparation process of the multilayer ceramic substrate, this strong bonding force ensures that the green body can maintain a specific shape during the molding process and prevents the separation and movement of the particles.

[0025] As a further technical solution, the dispersant includes one or both of sodium polyacrylate and triethyl phosphate.

[0026] In the present invention, the dispersant is added to effectively prevent the agglomeration of the particles and make them evenly dispersed in the slurry. This evenly dispersed state can ensure that the raw materials are fully contacted during the mixing process, laying the foundation for the subsequent formation of a uniform microstructure.

[0027] The present invention also provides a method for preparing a low dielectric loss multilayer ceramic substrate, comprising the following steps: S1, mixing alumina, a plasticizer, a sintering aid, a dispersant, and water to obtain a mixture; S2, adding a binder to the mixture to obtain a slurry, and performing tape casting to obtain a green porcelain sheet; S3, after punching holes in the green ceramic sheet, surface printing, lamination, upper and lower conduction, cutting, sintering, and cooling, a multilayer ceramic substrate is obtained.

[0028] As a further technical solution, the number of the stacked layers is 30 to 60 layers.

[0029] As a further technical solution, the shape of the punched hole in S3 is circular, and the diameter of the circle is 100-150 μm.

[0030] As a further technical solution, the raw material for the surface printing in S3 is tungsten paste, and the thickness of the surface printing is 15-20 μm.

[0031] In the present invention, tungsten paste is used as the printing material. Tungsten has a high electrical conductivity. Surface printing using tungsten paste can form a conductive circuit on the surface of a multilayer ceramic substrate. The conductive layer formed by the tungsten paste has a low resistance, which can effectively reduce the heat loss of electric energy during transmission and avoid performance degradation due to overheating.

[0032] As a further technical solution, the sintering temperature in S3 is 800-900° C., the sintering time is 30-60 min, and the sintering atmosphere is air.

[0033] The working principle and beneficial effects of the present invention are: In the present invention, alumina is used as a raw material, and a multilayer ceramic substrate is prepared by reasonably matching plasticizers, binders, sintering aids and dispersants. The plasticizer gives the substrate a certain flexibility, effectively improves its brittleness, and enables the substrate to better resist external force impact during processing and use, reducing the risk of cracking; the binder enhances the bonding force between the components, greatly improves the overall structural strength and stability of the substrate, and ensures that good physical form and performance can be maintained under complex environments; the sintering aid can reduce the sintering temperature, promote densification, and optimize the microstructure of the ceramic substrate; the dispersant can improve the fluidity of the slurry, ensure that the thickness of the substrate after molding is uniform, the surface is flat, and internal defects are reduced; the present invention uses the first alumina and the second alumina of different forms at the same time, and exerts the synergistic effect of the two, so that the microstructure of the ceramic substrate is more compact, the pores and defects inside the ceramic substrate are reduced, and the dielectric loss of the multilayer ceramic substrate is reduced. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the following examples and comparative examples: First alumina: spherical alumina, average particle size is 3~5μm; Second aluminum oxide: flake aluminum oxide, with an average particle size of 3nm; Calcium oxide: fineness is 325 mesh; Yttrium oxide: average particle size 1 μm; Cerium oxide: average particle size 1 μm; Number of stacking layers: 30; Surface printing thickness: 15μm.

[0036] Example 1 A method for preparing a low dielectric loss multilayer ceramic substrate comprises the following steps: S1, weighing 90 parts of aluminum oxide, 1 part of dibutyl phthalate, 3 parts of calcium oxide, 1 part of triethyl phosphate, and 50 parts of water, and stirring to obtain a mixture, wherein the aluminum oxide consists of a first aluminum oxide and a second aluminum oxide in a mass ratio of 2:1; S2, adding 6 parts of acrylate to the mixture, stirring to obtain slurry, and casting the slurry to obtain a green porcelain sheet; S3. After punching the raw ceramic sheets, a through hole with a diameter of 100 μm is formed. After printing tungsten paste with a thickness of 20 μm on the surface, 30 raw ceramic sheets are stacked together with a stacking pressure of 10 MPa. After the upper and lower parts are connected, they are cut and sintered at a temperature of 800°C for 60 minutes in an air atmosphere. After cooling, a multilayer ceramic substrate is obtained.

[0037] Example 2 A method for preparing a low dielectric loss multilayer ceramic substrate comprises the following steps: S1, weighing 95 parts of aluminum oxide, 2 parts of dioctyl phthalate, 4 parts of yttrium oxide, 2 parts of triethyl phosphate, and 55 parts of water, and stirring to obtain a mixture, wherein the aluminum oxide is composed of a first aluminum oxide and a second aluminum oxide in a mass ratio of 2:1; S2, adding 8 parts of acrylate to the mixture, stirring to obtain slurry, and casting the slurry to obtain a green porcelain sheet; S3. After punching the raw ceramic sheets, a through hole with a diameter of 120 μm is formed. After printing tungsten paste with a thickness of 15 μm on the surface, 30 raw ceramic sheets are stacked together with a stacking pressure of 10 MPa. After the upper and lower parts are connected, they are cut and sintered at a temperature of 850°C for 45 minutes in an air atmosphere. After cooling, a multilayer ceramic substrate is obtained.

[0038] Example 3 A method for preparing a low dielectric loss multilayer ceramic substrate comprises the following steps: S1, weighing 100 parts of aluminum oxide, 3 parts of dioctyl phthalate, 5 parts of cerium oxide, 3 parts of triethyl phosphate, and 60 parts of water, and stirring to obtain a mixture, wherein the aluminum oxide is composed of a first aluminum oxide and a second aluminum oxide in a mass ratio of 2:1; S2, adding 10 parts of acrylate to the mixture, stirring to obtain slurry, and casting the slurry to obtain a green porcelain sheet; S3. After punching the raw ceramic sheets, a through hole with a diameter of 150μm is formed. After printing tungsten paste with a thickness of 20μm on the surface, 30 raw ceramic sheets are stacked together with a stacking pressure of 10MPa. After the upper and lower parts are connected, they are cut and sintered at 900℃ for 30min in the air atmosphere. After cooling, a multilayer ceramic substrate is obtained.

[0039] Example 4 Compared with Example 3, the difference of Example 4 is that the aluminum oxide consists of a first aluminum oxide and a second aluminum oxide in a mass ratio of 3:1.

[0040] Example 5 The preparation method of the hydroxymethoxybenzaldehyde compound composite second aluminum oxide comprises the following steps: dispersing 5 parts of 4-hydroxy-2-methoxybenzaldehyde in 500 parts of anhydrous ethanol, adding 50 parts of the second aluminum oxide, mixing for 2 hours, filtering and drying, and obtaining the hydroxymethoxybenzaldehyde compound composite second aluminum oxide; Compared with Example 3, the difference of Example 5 is that the second alumina is replaced by an equal amount of a hydroxymethoxybenzaldehyde compound composite second alumina obtained by the above preparation method.

[0041] Example 6 Compared with Example 5, Example 6 is different in that 4-hydroxy-2-methoxybenzaldehyde is replaced by an equal amount of 2-hydroxy-4,5-dimethoxybenzaldehyde.

[0042] Example 7 Compared with Example 5, Example 7 is different in that 4-hydroxy-2-methoxybenzaldehyde is replaced by an equal amount of 4-hydroxy-2,6-dimethoxybenzaldehyde.

[0043] Example 8 Compared with Example 6, the difference in Example 8 is that the added amount of 2-hydroxy-4,5-dimethoxybenzaldehyde is 7.5 parts.

[0044] Example 9 Compared with Example 5, Example 9 is different in that 4-hydroxy-2-methoxybenzaldehyde is replaced by an equal amount of p-hydroxybenzaldehyde.

[0045] Comparative Example 1 Compared with Example 3, the difference in Comparative Example 1 is that the aluminum oxide is the first aluminum oxide.

[0046] Comparative Example 2 Compared with Example 3, the difference in Comparative Example 2 is that the aluminum oxide is the second aluminum oxide.

[0047] Experimental Example 1 The dielectric loss of the multilayer ceramic substrates prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was tested using a broadband dielectric impedance meter E4990A at a test frequency of 10 6 Hz, and read the dielectric loss value of the multilayer ceramic substrate.

[0048] The test results are shown in Table 1: Table 1 Performance test results of multilayer ceramic substrates prepared in Examples 1 to 4 and Comparative Examples 1 to 2

[0049] It can be seen from Table 1 that the dielectric loss of Examples 1 to 4 is less than that of Comparative Examples 1 and 2, indicating that the first aluminum oxide and the second aluminum oxide play a synergistic role and can reduce the dielectric loss of the multilayer ceramic substrate.

[0050] Experimental Example 2 The multilayer ceramic substrates prepared in Examples 3 and 5 to 9 were tested for bending strength according to the test method specified in GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics", and the test method was three-point bending.

[0051] The test results are shown in Table 2: Table 2 Performance test results of multilayer ceramic substrates prepared in Example 3 and Examples 5 to 9

[0052] As can be seen from Table 2, Examples 5 to 8 add hydroxymethoxybenzaldehyde compounds to composite the second alumina, and the bending strength of Examples 5 to 7 is higher than that of Examples 3 and 9, indicating that the addition of hydroxymethoxybenzaldehyde compounds to composite the second alumina can enhance the mechanical strength of the multilayer ceramic substrate.

[0053] Among Examples 5 to 7, the bending strength of Example 6 is higher than that of Examples 5 and 7, indicating that when the hydroxymethoxybenzaldehyde compound is 2-hydroxy-4,5-dimethoxybenzaldehyde, the obtained multilayer ceramic substrate has higher mechanical strength.

[0054] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low dielectric loss multilayer ceramic substrate, characterized in that: The method comprises the following raw materials in parts by weight: 90-100 parts of aluminum oxide, 1-3 parts of a plasticizer, 3-5 parts of a sintering aid, 6-10 parts of a binder, 1-3 parts of a dispersant, and 50-60 parts of water. The aluminum oxide consists of a first aluminum oxide and a second aluminum oxide, and the first aluminum oxide and the second aluminum oxide have different forms.

2. The low dielectric loss multilayer ceramic substrate according to claim 1, characterized in that: The first alumina is spherical alumina, the second alumina is flaky alumina, and the mass ratio of the first alumina to the second alumina is 2-3:

1.

3. The low dielectric loss multilayer ceramic substrate according to claim 1, characterized in that: The average particle size of the first aluminum oxide is 3-5 μm, and the average particle size of the second aluminum oxide is 3 nm.

4. The low dielectric loss multilayer ceramic substrate according to claim 1, characterized in that: The second aluminum oxide is a hydroxymethoxybenzaldehyde compound composite second aluminum oxide.

5. The low dielectric loss multilayer ceramic substrate according to claim 4, characterized in that: The hydroxymethoxybenzaldehyde compound includes one or more of 4-hydroxy-2-methoxybenzaldehyde, 2-hydroxy-4,5-dimethoxybenzaldehyde, and 4-hydroxy-2,6-dimethoxybenzaldehyde.

6. The low dielectric loss multilayer ceramic substrate according to claim 1, characterized in that: Also includes at least one of the following technical features: The plasticizer includes one or two of dibutyl phthalate and dioctyl phthalate; The sintering aid includes one or more of calcium oxide, yttrium oxide, and cerium oxide; The binder includes one or more of acrylate, polyvinyl alcohol, and polyvinyl butyral; The dispersant includes one or both of sodium polyacrylate and triethyl phosphate.

7. The method for preparing a low dielectric loss multilayer ceramic substrate according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing alumina, a plasticizer, a sintering aid, a dispersant, and water to obtain a mixture; S2, adding a binder to the mixture to obtain a slurry, and performing tape casting to obtain a green porcelain sheet; S3, after punching holes in the green ceramic sheet, surface printing, lamination, upper and lower conduction, cutting, sintering, and cooling, a multilayer ceramic substrate is obtained.

8. The method for preparing a low dielectric loss multilayer ceramic substrate according to claim 7, characterized in that: The shape of the punched hole in S3 is circular, and the diameter of the circle is 100-150 μm.

9. The method for preparing a low dielectric loss multilayer ceramic substrate according to claim 7, characterized in that: The raw material for surface printing in S3 is tungsten paste.

10. The method for preparing a low dielectric loss multilayer ceramic substrate according to claim 7, characterized in that: The sintering temperature in S3 is 800-900° C., the sintering time is 30-60 min, and the sintering atmosphere is air.

Citation Information

Patent Citations

  • Zirconia ceramic substrate for LED

    CN104987065A

  • Multi-layer aluminum oxide ceramic metallized tungsten slurry for HTCC and preparation method of multi-layer aluminum oxide ceramic metallized tungsten slurry

    CN114380624A

  • Alumina green ceramic chip for particulate matter sensor and preparation method of alumina green ceramic chip

    CN114804841A

  • High-strength low-dielectric composite microwave dielectric ceramic material and preparation method thereof

    CN116924774A

  • High-strength low-dielectric microwave dielectric ceramic material and preparation method thereof

    CN116924784A

Cited By

  • High-strength multilayer ceramic substrate and preparation method thereof

    CN119899021A

  • A high-strength multi-layer ceramic substrate and a preparation method thereof

    CN119899021B

  • Zero-shrinkage low-temperature co-fired multilayer ceramic substrate and preparation method thereof

    CN120208653A

  • High-strength wear-resistant multilayer ceramic substrate and preparation method thereof

    CN120554098A

  • High-strength wear-resistant multilayer ceramic substrate and method of making same

    CN120554098B